Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1111/j.1540-8159.2009.02599.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathology in Patients with ICDs over Time: Results of a Prospective Study

Abstract: Patients receiving ICDs have significant rates of baseline psychopathology after implantation. However, psychological assessment scores tend to improve with time. ICD shocks do not appear to significantly impact psychological state. These results suggest the importance of close screening and referral for possible psychopathology in patients receiving ICDs, especially in the peri-implant period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
81
4
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(95 citation statements)
references
References 37 publications
6
81
4
1
Order By: Relevance
“…10 These rates dropped significantly in the first 6 months after implantation to 12% and remained stable at 13% at 1 year. Despite an initial reduction in the number of patients with PTSD, a recent study found that 2 years after implant, there is a substantially greater prevalence of PTSD in ICD patients.…”
Section: Prevalence and Clinical Impact Of Ptsdmentioning
confidence: 99%
See 3 more Smart Citations
“…10 These rates dropped significantly in the first 6 months after implantation to 12% and remained stable at 13% at 1 year. Despite an initial reduction in the number of patients with PTSD, a recent study found that 2 years after implant, there is a substantially greater prevalence of PTSD in ICD patients.…”
Section: Prevalence and Clinical Impact Of Ptsdmentioning
confidence: 99%
“…24 Moreover, ICD patients with elevated PTSD scores after device implantation were significantly more likely to have shock storm. 10 Furthermore, elevated PTSD scores were associated with a 3.2 times greater likelihood of mortality within 5 years compared with ICD patients with no to moderate symptom levels of PTSD, even after controlling for disease and demographic parameters. 14 In addition to understanding the prevalence of psychosocial distress, possessing a working knowledge of the presentation of psychosocial distress in ICD patients is the most helpful method of facilitating appropriate intervention.…”
Section: Prevalence and Clinical Impact Of Ptsdmentioning
confidence: 99%
See 2 more Smart Citations
“…Doraźne leczenie powinno spowodować określenie przyczyny wyła-dowań urządzenia, natomiast ważnym uzupełnieniem jest leczenie dystresu psychologicznego [229]. Poziom stresu może być różny, ale u pacjentów mogą też występować bardziej nasilone postaci choroby, takie jak zespół stresu pourazowego [232,233], który wiąże się z wcześniejszymi wyładowaniami oraz stresem przed wszczepieniem ICD [234]. U pacjentów z niedawną tachyarytmią może również występować lęk w oczekiwaniu na kolejne wyładowanie [235].…”
Section: Psychospołeczne Następstwa Leczenia Za Pomocą Implantowanychunclassified